2016
DOI: 10.1007/s11219-016-9338-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated refinement of models for model-based testing using exploratory testing

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.Model-based testing relies on models of the system under test to automatically generate test cases. Consequently, the effectiveness of the generated test cases depends on models. In general, these models are created manually, and as such, they are subject to errors like omission of certain system usage behavior. Such omitted behaviors are also omitted by the generated test cases. In practice, these fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Also, Wang et al (2017) used model based testing to validate quorum-based systems implemented using the Gorums library through a new approach. On the other hand, some studies give the publications covering supporting techniques for modelling and test generation (Gebizli and Sozer, 2017), integration into industrial practice (Peleska, 2013), taxonomies (Utting et al, 2012), industrial evaluations (Blom et al, 2016), surveys and classification. For example Utting et al (2012) that have provided taxonomy of model based testing in which the principal aspects of MBT approaches are covered.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Wang et al (2017) used model based testing to validate quorum-based systems implemented using the Gorums library through a new approach. On the other hand, some studies give the publications covering supporting techniques for modelling and test generation (Gebizli and Sozer, 2017), integration into industrial practice (Peleska, 2013), taxonomies (Utting et al, 2012), industrial evaluations (Blom et al, 2016), surveys and classification. For example Utting et al (2012) that have provided taxonomy of model based testing in which the principal aspects of MBT approaches are covered.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also been reported on the development of test environments to support exploratory testing. For example, ARME enables the automatic re nement of system models based on recorded testing activities of test engineers (Gebizli and Sözer, 2016). Tapir supports team collaboration in exploratory testing and reconstruction of system models (Bures et al, 2018).…”
Section: Exploratory Testingmentioning
confidence: 99%
“…A Testdriven approach, which is a use case, has been chosen to validate the functional requirement [14]. Test engineer uses their knowledge and experience to create a test case [15]. The effectiveness of it has been proven in many cases.…”
Section: B Functional Requirement 1) Consistencymentioning
confidence: 99%
“…The effectiveness of it has been proven in many cases. The effectiveness of the generated test case depends on its correctness and completeness [15]. Test cases usually prepared during the requirement phase.…”
Section: B Functional Requirement 1) Consistencymentioning
confidence: 99%